Tinjauan Yuridis Pertanggungjawaban Pidana Bagi Seorang Pengidap Penyakit Gangguan Jiwa Halusinasi Dalam Tindak Pidana Pembunuhan - Lawra Esperanza Asyraf; Evi Deliana; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Stuart & Laraira defines hallucinations as a response from the five senses in the absence of external stimuli. Hallucinations are a perception disorder where the patient perceives something that is not actually happening. There are five types of hallucinations, namely hearing, vision, smell, taste and touch. Hearing hallucinations are the most common type of hallucinations found to occur. Murdered by the hallucination of unseen whispers classified as various and tend to be sadistic. Some perpetrators killed the victim with a long knife, there was also killed the victim by shooting the victim many times, there were even perpetrators who killed the victim by mutilating it. This research is a normative legal research, because it is based on library research that takes excerpts from reading books, literature, or supporting books that have relation to the problem to be studied, assisted with secondary data sources. This study uses qualitative data analysis and produces descriptive data. From the results of the study, it was concluded that, First, if the defendant cannot account for his actions, the judge handed down the verdict to release the defendant from all charges as regulated in Article 44 paragraph (1) of the Criminal Code, and the judge can order the defendant to enter a mental hospital for a maximum of one year. to be checked. Second, the criteria according to the law that is said to have hallucinatory mental illnesses according to article 44 of the Criminal Code are the contents of a foreign mind from the outside into his mind, the notion of himself is controlled by a certain force from outside, the hallucinatory voice that comments continuously, and the misunderstanding of the misunderstanding settled other types. Based on the results of psychiatric examinations performed by psychiatrists. The author's suggestion is, First, in Article 44 of the Criminal Code regarding the ability to be responsible more explained in more detail who can be said to be disturbed or mentally disabled so that they cannot be held liable for criminal liability or subject to criminal sanctions. Second, the judge should decide the case above also pay more attention not only to the results of the defendant's mental examination. But also pay attention to the testimonies of those closest to the defendant who do interact with the defendant on a daily basis. Keywords: Mental Disorders, Criminal Acts, Criminal Liability